Regulation of eosinophil recruitment and heterogeneity during allergic airway inflammation - Graf, Lisa-Marie; Radtke, Daniel; Voehringer, David (Frontiers in Allergy, 2025)
Eosinophils represent a granulocyte cell type that is strongly associated with type 2 inflammatory conditions. During steady state conditions few eosinophils are found in lung tissue, though they may contribute to homeostasis. In allergic airway inflammation, eosinophils are strongly increased and associated to disease severity. The underlying type 2 immune response tightly regulates eosinophil development, recruitment, survival, and heterogeneity. Inflammatory eosinophils in the lung are unfavourable, as they can cause tissue damage, amplify type 2 immunity and induce bronchial obstruction by expelling granular proteins and cytokines. In this review we provide an overview about mechanisms regulating development of eosinophils in the bone marrow and their extravasation into the lung including recent findings on induction and diversity of eosinophilia in allergic airway inflammation.